NIKAH SIRRI: DIMANA PEREMPUAN? - â€˜Ulya, Fina (Musawa Jurnal Studi Gender dan Islam, 2013)
Nikah sirri often make controvertion. People who reject nikah sirri and who receiveÂ  nikah sirri, all of them using religious texts to strengthen their opinion. Nikah sirri make problems than benefits, and almost women and children become victims. So, we have to solve this big problem, the important thing is rethinking and redefining marriage concept. Because, marriage often understood only relation two persons (male and female) with God. But actually the case is social problems. And what is more give knowledge for women, so they can be autonomous and be self-reliant.